USUL FIKIH: REKONSTRUKSI METODOLOGIS DALAM DINAMIKA HUKUM ISLAM - Efrinaldi Efrinaldi (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2018)
The philosophical-historical analysis on Islamic law amid the society is becoming an increasing focus of attention, especially for academicians. Their debates, to some extend, are nearly touching even the sacralized matter. But it is also regrettable that what  they have discussed so far are merely the problems on the surface and considered trivial as they do not touch  the core of the problem likes establishing a new-accepted and relevant theory. What they have done or discussed are merely repetitive. The point to be discussed here is the sacralization of the thoughts and blind following toward one  thought of school. Employing the philosophical-historical analysis on Islamic law and it relationship with the Islamic jurisprudence and comparing it with the contemporary methodology, this writing is aimed at looking for new formula on the Islamic  jurisprudence reasoning with the development of methodology of Islamic studies.